Unconditional respect for persons and the prediction of intergroup action tendencies - Lalljee, M; Tam, T; Hewstone, M; Laham, S; Lee, J (2009)
Unconditional respect for persons is an orientation that rests on the assumption that all people have intrinsic worth and deserve respect simply by their being human. This paper reports three cross-sectional studies concerning unconditional respect in intergroup relations in three very different contexts. In all three studies, unconditional respect was positively related to positive action tendencies, and negatively related to negative action tendencies, toward other groups. Regression analyses showed that respect was a significant predictor of negative action tendencies even when attitude to the other group, social dominance orientation, empathy, and the quality and quantity of intergroup contact were statistically controlled. Moderation analyses showed that respect was particularly important under conditions of high threat. The implications of unconditional respect for intergroup relations are discussed. Copyright © 2008 John Wiley and Sons, Ltd.